Preparation, characterization, and in vitro/vivo studies of oleanolic acid-loaded lactoferrin nanoparticles - Xia X; Liu H; Lv H; Zhang J; Zhou JP; Zhao Z (Drug Design, Development and Therapy, 2017)
Xiaojing Xia,1,2 Haowei Liu,1 Huixia Lv,1 Jing Zhang,1 Jianping Zhou,1 Zhiying Zhao3 1Department of Pharmaceutics, China Pharmaceutical University, Nanjing, 2Department of Pharmaceutics, ZheJiang Pharmaceutical College, Ningbo, 3Department of Traditional Chinese Medicine, China Pharmaceutical University, Nanjing, People’s Republic of China Abstract: Oleanolic acid (OA), a pentacyclic triterpene, is used to safely and economically treat hepatopathy. However, OA, a Biopharmaceutics Classification System IV category drug, has low bioavailability owing to low solubility (<1 µg/mL) and biomembrane permeability. We developed a novel OA nanoparticle (OA-NP)-loaded lactoferrin (Lf) nanodelivery system with enhanced in vitro OA dissolution and improved oral absorption and bioavailability. The OA-NPs were prepared using NP albumin-bound technology and characterized using dynamic light scattering, scanning electron microscopy, X-ray powder diffraction, differential scanning calorimetry, and in vitro dissolution test. The in vivo pharmacokinetics was investigated in Sprague Dawley rats using liquid chromatography-tandem mass spectrometry. OA-NPs (OA:Lf =1:6, w/w%) exhibited spherical morphology, 202.2±8.3 nm particle size, +(27.1±0.32) mV ζ potential, 92.59%±3.24% encapsulation efficiency, and desirable in vitro release profiles. An effective in vivo bioavailability (340.59%) was achieved compared to the free drug following oral administration to rats. The Lf novel nanodelivery vehicle enhanced the dissolution rate, intestinal absorption, and bioavailability of OA. These results demonstrate that Lf NPs are a new strategy for improving oral absorption and bioavailability of poorly soluble and poorly absorbed drugs. Keywords: oleanolic acid, nanoparticle, lactoferrin nanodelivery system, drug absorption, bioavailability